Environmental public interest litigation in Malaysia: the new face - Amir, Dalila; Mohamad Bahri, Nurwafa Atikah (Universiti Teknologi MARA (UiTM), 2023)
Environmental issues gained popularity in these recent years not only at the international level but also on the local Malaysian platform. The awareness of the importance of conserving and preserving the environment keeps increasing since the world is now in an endangered environmental crisis. The clashes between the need for state development and preserving the environment especially faced by developing countries like ours, is a continuous and unsettled battle. Moreover, the victim, the environment, is a silent creature that has no place in the court of law to address its grievances. That is why public interest litigation is the hope for this silent victim. The public should be given the locus standi to address the environmental issues since the matter concerns the interest of the public at large, though not directly affected by the said development. Environmental public interest litigation is not a new subject. However, the development in Malaysia is not very encouraging and is considered the least explored area of public interest litigation since the decision of the Supreme Court in Government of Malaysia v Lim Kit Siang and United Engineers (M) Bhd v Lim Kit Siang [1988] 2 MLJ 12 also known as ‘UEM case’. However, the new hope for the growth and development of environmental public interest litigation emerged after the Malaysian Trade Union Congress & Ors v Menteri Tenaga, Air dan Komunikasi & Anor [2014] 3 MLJ 145 decided by the Federal Court. It is crucial now for the judges sitting in the upper courts to exercise their judicial activism creatively and wisely. Employing doctrinal and analytical methods, this study aims to contribute to the growth of environmental public interest litigation discussion. Thus, it will also serve as a foundation for future research on environmental litigation